Processing of Semantic Ambiguity Based on Words Ontology - A Abou Shousha; Samir Hamada; Salwa Hamada; Mohammad Alshibli (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
This research provides an automatic treatment for the phenomenon of semantic Polysemy based on the ontology (meaning, accompaniment, and translation) of words and its effect on the applications of automatic processing of the Arabic language. Polysemy may have negative effect on these applications. This research works on finding the solutions that helps improving the level of the automatic treatment of the Arabic language at all levels through applying a descriptive analysis for a sample of 50 words with their different derivatives. This descriptive analysis suggests to the user the most probable meaning of a suitable context through analyzing the context and relying on verbal structure and collocations and then determine the morphological analysis and appropriate translation of the English language as well as the availability of some statistical data such as the probability that this meaning is the appropriate sense of other meanings, the number of possible meanings and other statistical data. This study clarifies that the main reason of the semantic polysemy phenomenon in the used texts is the absence of diacritics.  It was found that applying the proposed methodology in this paper on the ontological corpus helps to identify the exact sentences intended meaning by more than 80% accuracy.  As a result, this automatic processing will give the benefit to the searching sites like Google, and also in facilitating the teaching of significance; especially in the field of metaphor "الاستعارة" in the Arabic language for non-native Arabic speakers. Moreover, it will help in analyzing the Arabic texts and translating and many other applications of Arabic language computing.